[Retracted] Microalgae as a Renewable Source of Energy: A Niche Opportunity - Jegathese, Simon Jegan Porphy; Farid, Mohammed (Journal of Renewable Energy, 2014)
Algae are believed to be a good source of renewable energy because of its rapid growth rate and its ability to be cultivated in waste water or waste land. Several companies and government agencies are making efforts to reduce capital cost and operating costs and make algae fuel production commercially viable. Algae are the fastest growing plant and theoretically have the potential to produce more oil or biomass per acre when compared to other crops and plants. However, the energy efficiency ratio and carbon and water footprint for algal based biofuels still need to be evaluated in order to fully understand the environmental impact of algal derived biofuels.